Physicochemical properties, urocanic acid and biogenic amine contents of black pomfret (Parastromateus niger) as affected by fermentation times - M. Azman, E.; Zare, D.; Nurhayati, Y.; Karim, R.; Ghazali, H. M. (Rynnye Lyan Resources, 2024)
Fermented freshwater and marine products are popular in Malaysia and among these is ikan pekasam (fermented fish). It is typically made from freshwater fish with groundroasted rice as the main source of carbohydrate during fermentation. In this study, rather than freshwater fish, black pomfret (Parastromateus niger), a marine fish, was used to produce ikan pekasam. Black pomfret was mixed with 3 kg of ground roasted rice and 10% (v/w of fish) water and allowed to ferment for 2 and 5 weeks at 25 – 30°C. Then, fermented black pomfret was analysed for its physicochemical properties, compositions of biogenic amine, urocanic acid (UCA) and organic acid, as well as sensory acceptability. The pH and titratable acidity significantly (p ≤ 0.05) decreased and increased, respectively, after 5 weeks of fermentation due to the increase in organic acids, mainly lactic acid. Histamine, putrescine, cadaverine and 2-phenylethylamine increased rapidly after 5 weeks of fermentation but histamine was within the recommended level (50 mg/kg; US Food and Drug Administration (USFDA)). The strong correlation between trans- and cis-urocanic acid indicated that photoisomerization of trans-UCA into cis-UCA occurred. Overall, principal component analysis (PCA) revealed that the two-week fermented black pomfret was more acceptable to the consumer panellists than the five-week due to its acceptable aroma, saltiness, sourness and texture. Notably, this two-week sample had significantly (p ≤ 0.05) lower biogenic amine and UCA contents; suggesting a safer and good quality of ikan pekasam.